Use the four-step process to find \( f^{\prime}(x) \) and then find \( I^{\prime}(1), I^{\prime}(2) \), and \( f^{\prime}(3) \) \( f^{f}(x)=2 x^{2}-5 x+3 \) \( f^{\prime}(x)=\square \) \( f^{\prime}(1)=\square \) (Type an integer or a simplified fraction.) \( f^{\prime}(2)=\square \) (Type an integer or a simplified fraction.) \( f^{\prime}(3)=\square \) (Type an integer or a simplified fraction.)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To find \( f^{\prime}(x) \) from the function \( f(x) = 2x^{2} - 5x + 3 \), we'll follow the four-step process of differentiation: 1. **Identify the Function**: \( f(x) = 2x^{2} - 5x + 3 \). 2. **Apply the Power Rule**: The derivative of \( x^{n} \) is \( n \cdot x^{n-1} \). Thus: - The derivative of \( 2x^2 \) is \( 2 \cdot 2x^{2-1} = 4x \). - The derivative of \( -5x \) is \( -5 \). - The derivative of a constant (3) is \( 0 \). 3. **Combine the Results**: So, \( f^{\prime}(x) = 4x - 5 \). 4. **Conclusion**: Therefore, \( f^{\prime}(x) = 4x - 5 \). Now to find \( f^{\prime}(1) \), \( f^{\prime}(2) \), and \( f^{\prime}(3) \): - \( f^{\prime}(1) = 4(1) - 5 = 4 - 5 = -1 \). - \( f^{\prime}(2) = 4(2) - 5 = 8 - 5 = 3 \). - \( f^{\prime}(3) = 4(3) - 5 = 12 - 5 = 7 \). So, the final answers are: - \( f^{\prime}(x) = 4x - 5 \) - \( f^{\prime}(1) = -1 \) - \( f^{\prime}(2) = 3 \) - \( f^{\prime}(3) = 7 \)